miR-181a-5p Inhibits Pyroptosis in Sepsis-Induced Acute Kidney Injury through Downregulation of NEK7 - Meng Zhang; Deyuan Zhi; Jin Lin; Pei Liu; Yajun Wang; Meili Duan (Journal of Immunology Research)
Sepsis is a life-threatening organ dysfunction caused by the uncontrolled inflammation, easily affecting the kidney. Sepsis-induced acute kidney injury (S-AKI) has high morbidity and mortality, of which the pathophysiological mechanisms have not been completely illuminated, leading to nonspecific therapies. Specific microRNAs were related with the pathogenesis of AKI. However, only limited studies focused on the pyroptosis in the context of S-AKI. The in vitro LPS-induced HK-2 cell model and in vivo CLP-induced mouse model were established. qRT-PCR, Western blot, ELISA, and RNA pulldown were used for expression examination. Multiple biological databases were used for miRNA screening. H&E staining and IHC staining were performed. The LPS-induced HK-2 cells showed significantly increased (P<0.01) fluorescence intensity of N-GSDMD and ASC compared with the HK-2 cells. The expression of NLRP3, NEK7, ASC, active caspase-1, and N-GSDMD was significantly enhanced (P<0.05) and the inflammatory factors including IL-18, IL-1β, and THF-α were all increased in LPS-induced HK-2 cells and CLP-induced mice. Renal edema, serum Cr and BUN, and expression of KIM-1 and NGAL were significantly higher (P<0.05) in CLP-induced S-AKI mice than the sham group. miR-101-3p, miR-144-3p, miR-181a-5p, miR-4262, and miR-513b-5p could inhibit NEK7. NEK7 is an interacting protein of miRNA-181a-5p. miR-181a-5p inhibits pyroptosis of the LPS-induced HK-2 cells through downregulation of NEK7. Pyroptosis of HK-2 cells promotes inflammation. miR-181a-5p inhibits pyroptosis through downregulation of NEK7 in LPS-induced HK-2 cells and CLP-induced mice. Our study indicated miR-181a-5p as a new potential therapeutic target for S-AKI therapy.